(untitled) (Journal of Engineering, 2005)
The most efficient nozzle is generally considered to be that for which the discharge coefficient is nearly unity. Nozzle dimensions influence the discharge coefficient. In sprinkler irrigation systems there are many types of nozzles because any sprinkler irrigation system has special one depend on these system characteristics, so the discharge coefficient relation with nozzle dimensions must be known to the sprinkler irrigation system designer. A computer program for nozzle flow characteristic was built and the relation between the discharge coefficient (C) and the nozzle geometrical dimensions to reach to the best nozzle design was studied. The finite -lifference approach was introduced to carryout all computations with special grid arrangement. The steady state Navier-Stocks equations complemented with (k-) turbulence models were solved. These work calculations were for nozzle of convergent part with some angle (3.7°-7.7°) followed by straight part (tip part). Three values were taken for the convergent part length; three for tip part length and the nozzle diameter changed for three values also. The Reynolds number range was 1.95 ×10 (Re(3.9 x10 and Fortran 95 computer program language was used. The results gave good imaging to the reiation between nozzle dimensions and the discharge coefficient, where the major result was Increasing the tip length is allowing the boundary layer to growth and hence increasing its thickness and so discharge coefficient decreasing. Comparison of the results with ANSYS package shows that the present numerical method was accurate enough and might be used to predict the discharge coefficient for the sprinkler irrigation system nozzle.